Influence of Particle Size of Enogen Feed High Amylase and Conventional Yellow Dent Corn on Nursery Pig Performance - H. R. Williams; H. R. Kerkaert; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey; S. S. Dritz; C. B. Paulk; H. I. Calderón (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 360 pigs (DNA 200 × 400; initially 14.5 lb) were used in a 35-d growth trial to evaluate the influence of particle size of Enogen Feed high amylase (Enogen, Syngenta Seeds, LLC, Downers Grove, IL) and conventional yellow dent corn on nursery pig performance. Pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted by weight to 1 of 6 dietary treatments in a randomized complete block design with 12 pens per treatment. Treatments were arranged in a 2 × 3 factorial with main effects of corn source (high amylase or conventional yellow dent) and 3 ground corn particle sizes (300, 600, or 900 microns). All pigs were fed a common pelleted diet for 7 days after weaning, then switched to experimental diets. Overall, from d 0 to 35, there were no differences among corn sources observed for average daily gain (ADG). As particle size of the diet increased, there was a tendency (quadratic,P= 0.074) for ADG to be similar for pigs fed 300- and 600-micron ground corn, but ADG decreased for pigs fed corn ground to 900 microns. There was a tendency (P= 0.086) for a corn source × particle size interaction for average daily feed intake (ADFI), with no change in ADFI for pigs fed conventional yellow dent corn, but a quadratic increase then decrease in ADFI for pigs fed high amylase corn. For feed efficiency (F/G), there was also a corn source × particle size interaction (P= 0.027) observed with improved F/G as particle size was reduced for high amylase corn, but not for conventional yellow dent corn. In summary, reducing particle size of high amylase corn improves feed efficiency with no major differences between corn sources for overall daily gain.
Keywords: corn; high amylase; nursery pigs; particle size